Can the Application of the Human Rights of the Child in a Criminal Case Result in a Therapeutic Outcome - Coetzee, Enid (Potchefstroom Electronic Law Journal, 2017)
Prior to the change brought about by S v M,[1] the interests of children were only considered as a circumstance or mitigating factor of the offender during the sentencing process. The article will discuss case law in order to determine the impact that the inclusion of the human rights of the child had on the sentencing process if the offender was the primary caregiver of the child. Specific reference is made to Sections 28(2) and 28(1)(b) of the Constitution of the Republic of South Africa, 1996. The article will then consider whether this inclusion might improve therapeutic outcomes without the apprehension that the interests of justice would be forfeited. A therapeutic outcome is brought about when the attention is placed on the human, emotional and psychological side of the law. It is concluded that the Zinn triad remains the basic measure to be used by sentencing courts to determine an appropriate sentence. Should the sentence be direct imprisonment, the court has to ensure that the children receive appropriate care as prescribed by Section 28(1)(b). Should a range of sentences be considered, even though the court has a wide discretion to decide which factors should be allowed to influence the measure of punishment, when the offender is a primary caregiver, Section 28(2) must be included as an independent factor. It is also concluded from the case law discussion that the inclusion of the human rights of the child in the sentencing process did not automatically give rise to a therapeutic outcome, although in some judgments it did result in a therapeutic outcome. Thus, the consideration of the human rights of the children during the sentencing process creates the opportunity for a therapeutic outcome.